PERAN STRATEGIS MANAJEMEN HUMAS DAN LAYANAN PUBLIK DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI SEKOLAH - Marpaung, Syafri Fadillah; Febrianti, Indri; Simatupang, Siti Fatimah Azzahro; Aidin, Winda; Wibowo, M. Padeli; Almaajid, Rizqi (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to analyze the strategic role of public relations management and public services in improving the quality of education in schools. The research method used is library research or library research. Through this approach, researchers conduct a search and analysis of literature sources that are relevant and related to the research topic. Effective public relations management can strengthen school relationships with stakeholders and increase understanding of education goals, policies, and programs. In addition, this research also studies the role of public services in providing quality services to the school community. The results of this study provide a more comprehensive understanding of the importance of effective management of public relations and public services in improving the quality of education, as well as providing practical recommendations for practitioners and decision makers in the field of education to improve existing policies and practices.